Living images
1 online resource (318 pages).
Keywords: The haunting funerary paintings on wood coffins found in Roman Egypt still represent some of the most vivid images that come to us from the ancient world. These paintings were first discovered by Flinders Petrie, father of modern archaeology, in his excavations in the Egyptian Fayum during the 1880s and have rested at University College London for over 100 years. Now, the Petrie Museum is bringing this corpus of paintings to the public in a stunning catalog. Living Images is a beautiful and authoritative presentation of the restored collection that will be an essential reference for scholars and a fascinating read for general audiences. Central to the volume is a complete catalog of the mummy portraits uncovered by Petrie, including full color illustrations and descriptions of technical and stylistic features and iconographic characteristics. To add to the value of the volume, articles describe the process of finding the mummies, explain the place of funerary assemblages in the history of Egyptian burial customs, offer an introduction to Egyptian portrait painting, and explain the conservation issues presented by the coffins. Petrie’s own reflections on his finds are also included. The volume is dedicated to the memory of Egyptologist Barbara Adams and co-sponsored by the Petrie Museum.